1995
DOI: 10.1073/pnas.92.20.9427
|View full text |Cite
|
Sign up to set email alerts
|

Multiple N-acyl-L-homoserine lactone signal molecules regulate production of virulence determinants and secondary metabolites in Pseudomonas aeruginosa.

Abstract: Pseudomonas aeruginosa produces a spectrum of exoproducts many of which have been implicated in the pathogenesis of human infection. Expression of some of these factors requires cell-cell communication involving the interaction of a small diffusible molecule, an "autoinducer," with a positive transcriptional activator. In P. aeruginosa PAO1, LasI directs the synthesis of the autoinducer N-(3-oxododecanoyl)-L-homoserine lactone (OdDHL), which activates the positive transcriptional activator, LasR. Recently, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
381
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(391 citation statements)
references
References 32 publications
8
381
1
1
Order By: Relevance
“…Thus it has been shown that N-(3-oxododecanoyl)-L-homoserine lactone (OdDHL), a quorumsensing signal molecule (QSSM) from P. aeruginosa (Winson et al, 1995;Pesci et al, 1997), can suppress immune responses of the type commonly associated with antibacterial immunity and the development of autoimmune disease (Telford et al, 1998). Other data suggest that these molecules may also stimulate proinflammatory activity (Smith et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus it has been shown that N-(3-oxododecanoyl)-L-homoserine lactone (OdDHL), a quorumsensing signal molecule (QSSM) from P. aeruginosa (Winson et al, 1995;Pesci et al, 1997), can suppress immune responses of the type commonly associated with antibacterial immunity and the development of autoimmune disease (Telford et al, 1998). Other data suggest that these molecules may also stimulate proinflammatory activity (Smith et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…LasR has a positive effect on RhlR expression. RhlR, with its cognate autoinducer BHL, positively regulates the expression of the rhlI (vsmI ) gene (Latifi et al, 1996), which in turn is assumed to direct the synthesis of BHL (Ochsner and Reiser, 1995;Winson et al, 1995). Culture supernatants of strain PAO1, PAO6281 and PAO6281/ pME6117 grown in glycerol-alanine medium were analysed for BHL by high-performance liquid chromatography (HPLC).…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of the transcriptional activator LasR, OdDHL stimulates the production of the exoenzymes elastase, alkaline protease, and toxin A Pearson et al, 1994;Rust et al, 1996). A second signal molecule of P. aeruginosa, N-butyryl-homoserine lactone (BHL), whose synthesis depends on the rhlI (vsmI ) gene (Ochsner and Reiser, 1995;Pearson et al, 1995;Winson et al, 1995), co-operates with the regulator RhlR (VsmR) to enhance the production of rhamnolipid (a heat-stable haemolysin), pyocyanin, cyanide, and lipase (Ochsner et al, 1994;Latifi et al, 1995;Jaeger et al, 1996); the same autoinducer system also contributes to the formation of elastase and alkaline protease (Pearson et al, 1995;Brint and Ohman, 1995;Latifi et al, 1995). The activator LasR has a positive effect on the expression of rhlR and rhlI (Latifi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown recently that the RsmA in A. vinelandii represses post-transcriptionally the expression of PhbR, a transcriptional regulator that activates the phbBAC operon encoding the PHB-synthesis enzymes (Hernandez-Eligio et al, 2012). In the case of P. aeruginosa PAO1, however, it has been suggested that the GacS/GacA TCS regulates the production of AHLs, which have a positive effect upon the induction of rpoS expression, which in turn activates genes expressed mainly during the stationary phase, such as those encoding the production of several virulence factors, including pyocyanine, exotoxin A, elastase and lipase enzymes and type III secretion system among others (Hogardt et al, 2004;Latifi et al, 1995;Reimmann et al, 1997;Winson et al, 1995;Winzer et al, 2000). Furthermore, it has been reported that this signal transduction system in this bacterium acts exclusively by controlling the transcription of the RsmY and RsmZ regulatory small RNAs (Brencic et al, 2009).…”
Section: Discussionmentioning
confidence: 99%